LARVAL MOSQUITO FAUNA (DIPTERA: CULICIDAE) IN DUSUN IV GOSOMA VILLAGE, NORTH HALMAHERA - FIktor Imanuel Boleu; Harsen Berg Janis; Jubhar Christian Mangimbulude (Faculty of Public Health, Sriwijaya University, 2019)
Abstract North Halmahera Region is not categorized in the list of higher regions of dengue fever in Indonesia. However, in the last few years, the occurrence of fever dengue in this region tend to increased. To get basic information in order to find the proper strategy for dengue fever control, a survey of mosquito larvae in the Dusun IV Gosoma village, North Halmahera have been done with the purpose was to determined the types and density of mosquito larvae.The research was cross-sectional designed, it was held at July and August 2018 in Dusun IV Gosoma Village, District of Tobelo, North Halmahera region. The mosquito larvae was checked at the containers as potential breeding place using single larvae methods. The larvae was identified in Integrated Science laboratory, University of Halmahera. The identified larvae was used to calculate Container Index (CI), House Index (HI) and Free Larvae Number. Temperature, moisture light intensity and pH were measured in sites. A survey of mosquito larvae at 35 of houses which is have 100 of containers. Only two types of mosquito were found, Aedes aegypti (91, 67%) and Culex pipiens pipiens (8,33%). Larvae index in Dusun IV Gosoma village was calculated, House Index (HI), Container Index (CI) and Free Larvae Number were 37.14%, 22% and 62.86% respectively. This indicating potential risk for dengue fever transmission in that region. The average of temperature, moisture, light intensity in the location of Ae. aegypti found were 29.75 oC, 77.50% dan 1890 lux respectively. While the average temperature and pH within the containers positive Ae. aegypti were 27.5 oC dan 6.93 respectively. The average of temperature, moisture, light intensity in the location of Cx. pipiens pipiens found were 30,75 oC, 75,50% dan 1734,5 lux respectively. While the average temperature and pH within the containers positive Cx. pipiens pipiens were 28 oC dan 7,5 respectively. The types of mosquitoes found in the Dusun IV ​​Gosoma Village are Ae. aegypti and Cx. pipiens pipiens. Ae. aegypti mosquito is more dominant and has a high enough density so that it can be potentially affect the spread of DHF. Keywords: Aedes aegypti, Culex pipiens pipiens, DHF, larvae index, north halmahera